2005
DOI: 10.3998/ark.5550190.0006.410
|View full text |Cite
|
Sign up to set email alerts
|

Trans-2-aminocyclohexanols as pH-triggered molecular switches

Abstract: Cyclohexane-based conformationally controlled ionophores, the emerging new class of molecular switches, provide a new and promising approach to allosteric systems with negative cooperativity. Protonation of trans-2-aminocyclohexanols leads to dramatic conformational changes: due to an intramolecular hydrogen bond, a conformer with equatorial position of ammonio-and hydroxy-groups becomes predominant. Thus, these structures can serve as powerful conformational pH-triggers. The trans-2-aminocyclohexanol moiety h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Thus, the elongation and branching of the hydrocarbon chains did not produce any conformational effects in the polar heads of these structures. In accordance with the previous observations for various trans-2-morpholinocyclohexanols [13,14,[23][24][25][26], the molecules of 1-3 strongly prefer the conformation B (Scheme 3) in a nonpolar solvent (CDCl 3 ) thanks to the stabilizing intramolecular hydrogen bond OH…N. The hydrogen bonds of this type were found to be strong enough to convert a chair ring into a twist-boat conformation in aminohydroxy steroids [29,30].…”
Section: The Conformer Populations (N a N B ) In The Fast Equilibrium [A + Ah + ]supporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the elongation and branching of the hydrocarbon chains did not produce any conformational effects in the polar heads of these structures. In accordance with the previous observations for various trans-2-morpholinocyclohexanols [13,14,[23][24][25][26], the molecules of 1-3 strongly prefer the conformation B (Scheme 3) in a nonpolar solvent (CDCl 3 ) thanks to the stabilizing intramolecular hydrogen bond OH…N. The hydrogen bonds of this type were found to be strong enough to convert a chair ring into a twist-boat conformation in aminohydroxy steroids [29,30].…”
Section: The Conformer Populations (N a N B ) In The Fast Equilibrium [A + Ah + ]supporting
confidence: 88%
“…[B + BH + ] (Scheme 3) were calculated as described before for (amino)cyclohexanol derivatives [13,14,[22][23][24][25][26][27] from an averaged signal width (W = ΣJ HH ) measured as the distance between terminal peaks of a multiplet in the 1 H NMR spectrum: W observed = W A •n A + W B •n B [28] (Table 1). We used mainly the signal of H4 (geminal to the hydroxy group, Scheme 3), which was usually better resolved and located in a region apart from other signals.…”
Section: The Conformer Populations (N a N B ) In The Fast Equilibrium [A + Ah + ]mentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectroscopy did not allow determination of the ratio of meso-2 and rac-2 in the product mixture thus obtained because both diastereoisomers give rise to indistinguishable NMR spectra, even in the presence of salts such as KBr whose cation can bind to these bis(crown ethers) [15]. HPLC, on the other hand, allowed determination of the diastereomeric ratio provided that the mobile phase contains KBr [see ESI].…”
mentioning
confidence: 99%
“…For the preparation of pH-sensitive liposomes [3,11,[75][76][77], some researchers have used a polyacrylic acid, polyethylene glycol-ortho ester-distearoyl glycerol conjugate (POD), trans-2-aminocyclohexanols [78], N-hemisuccinate-dioleoyl-phosphatidylethanolamine [79]. Nancy L. Bomane et al [80] in the research with large unilamellar vesicle (LUV) showed that increasing the (saturated) the length of the acyl chain of phosphatidylcholine molecule increased the internal buffer capacity and made lower internal pH; all these lead to increased drugs retention time (VCR).…”
Section: Introductionmentioning
confidence: 99%